Determinants of psychosocial well‑being of older adults in Sarawak, Malaysia - Jeffery, Stephen; Sam Froze, Jiee; Azimah, Azman; Md Mizanur, Rahman; Rosalia, Saimon; Gui, Hun Chuen; Hee, Lim S.; Romano, Ngui (Wolters Kluwer – Medknow, 2025)
BACKGROUND: Malaysia’s rapid demographic shift toward an ageing society poses significant public health challenges, particularly with respect to psychosocial well‑being. Sarawak, an ethnically diverse state, faces unique issues related to household dynamics, ageing, and urbanization. This study aimed to describe the sociodemographic characteristics of older adults in urban Sarawak and assess their association with psychosocial well‑being. MATERIALS AND METHODS: The cross‑sectional study involved 766 older adults aged 60 and above in Kuching and Sibu. Participants were selected using multistage stratified random sampling and were interviewed using a structured, interviewer‑administered questionnaire. The mental health continuum–short form was utilized to assess their psychosocial well‑being, which was classified into poor, moderate, and good categories. Associations with sociodemographic factors were analyzed using Chi‑square tests and ordinal logistic regression. RESULTS: Of the 766 respondents, 50.8% were male, and 45.7% were aged 60–64 years. The prevalence of poor, moderate, and good psychosocial well‑being was 37.2%, 31.9%, and 30.9%, respectively. Age group and household size were significantly associated with well‑being (P < 0.05). Younger respondents (60–64 years) were more likely to report good well‑being (odds ratio [OR] = 1.78; 95% confidence interval [CI]: 1.13–2.81; P = 0.013), while smaller household size reduced the likelihood of poor well‑being (OR = 0.55; 95% CI: 0.33–0.91; P = 0.019). CONCLUSION: Recognizing that age and household size influence the psychosocial well‑being of older adults in Sarawak presents an opportunity for constructive intervention. Tailoring age‑specific programs to the context of urban, multigenerational living can effectively promote healthy ageing. By focusing on family engagement, community support, and access to resources, we can enhance resilience and improve the general standard of living for older adults in these environments.